Public financial management and Its emerging architecture - Cangiano, M. (Marco); Curristine, Teresa, 1970-; Lazare, Michel (International Monetary Fund, 2013)
The first two decades of the twenty-first century have witnessed an influx of innovations and reforms in public financial management. The current wave of reforms is markedly different from those in the past, owing to the sheer number of innovations, their widespread adoption, and the sense that they add up to a fundamental change in the way governments manage public money. This book takes stock of the most important innovations that have emerged over the past two decades, including fiscal responsibility legislation, fiscal rules, medium-term budget frameworks, fiscal councils, fiscal risk management techniques, performance budgeting, and accrual reporting and accounting. Not merely a handbook or manual describing practices in the field, the volume instead poses critical questions about innovations; the issues and challenges that have appeared along the way, including those associated with the global economic crisis; and how the ground can be prepared for the next generation of public financial management reforms.